Development Strategy Of Omah Kopi Banyuwangi Luwak Coffee Business - Setyawan, Bagus; Utami, Arfiati Ulfa; Ulfa, Rosiana; Arista, Yuvita Lira (AGRIBUSINESS JOURNAL, 2024)
Luwak coffee is one type of coffee that is currently one of the most popular variants for coffee-loving consumers. The existence of civet coffee-based businesses is also increasing, including the Kopi Luwak business Omah Kopi in Banyuwangi. The number of civet coffee processing agro-industries that have sprung up, technological developments and people's lifestyles make the Luwak Coffee Agroindustry "Omah Kopi" have to continue to innovate to survive. Based on this phenomenon, the research objectives to be examined are to determine the strategic position and development strategy of the "Omah Kopi" agroindustry. The location of this research is at Agroindustry Kopi Luwak "Omah Kopi" Banyuwangi. A quantitative description approach is used in the research method, using survey methods. The sampling method uses purposive sampling method. The data analysis method uses SWOT analysis. Based on the results of the study, it shows that the Banyuwangi "omah Kopi" agroindustry is in a strong position with opportunities (white area) in the growth / stability quadrant so that the right strategy to do is with a strategy that maximizes its strengths and opportunities. The conclusion of this study is that the civet coffee agroindustry "Omah kopi" is feasible to continue to be developed to become one of the quality civet coffee processing businesses in Banyuwangi both in the local and international markets